2005
DOI: 10.1029/2004jb003191
|View full text |Cite
|
Sign up to set email alerts
|

Rupture dynamics with energy loss outside the slip zone

Abstract: [1] Energy loss in a fault damage zone, outside the slip zone, contributes to the fracture energy that determines rupture velocity of an earthquake. A nonelastic two-dimensional dynamic calculation is done in which the slip zone is modeled as a fault plane and material off the fault is subject to a Coulomb yield condition. In a mode 2 crack-like solution in which an abrupt uniform drop of shear traction on the fault spreads from a point, Coulomb yielding occurs on the extensional side of the fault. Plastic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
401
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 331 publications
(429 citation statements)
references
References 25 publications
25
401
3
Order By: Relevance
“…[9] We checked that in mode II, considering the homogeneous properties, we retrieved the same slip velocity limitation, the same asymmetric lateral extension of the plasticity after 2 km of propagation and the same linear dependency of the off-fault fracture energy with rupture length as found by Andrews [2005].…”
Section: Numerical Modeling and Homogeneous Fault Validation Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…[9] We checked that in mode II, considering the homogeneous properties, we retrieved the same slip velocity limitation, the same asymmetric lateral extension of the plasticity after 2 km of propagation and the same linear dependency of the off-fault fracture energy with rupture length as found by Andrews [2005].…”
Section: Numerical Modeling and Homogeneous Fault Validation Testsmentioning
confidence: 99%
“…That is the reason why the constitutive law on the fault has been changed to a higher fracture energy and lower loading stress. This modification decreases the crack instability (increase of both S and d c ) before the strength change, compared to the original values of Andrews [2005]. We found that this combination of parameters, used for the homogeneous case study, leads to a too unstable rupture (for instance, the terminal velocity is reached very quickly), that is not likely to be stopped only by a small change of friction on the main rupture plane (considering that our fault is very smooth before the friction change, hence far from the critical state when reaching this point).…”
Section: Fracture Energy Change On the Main Fault Planementioning
confidence: 99%
See 3 more Smart Citations